Identification of lactic acid bacteria strains modulating incretin hormone secretion and gene expression in enteroendocrine cells. (May 2016) - Panwar, Harsh; Calderwood, Danielle; Gillespie, Anna L.; Wylie, Alastair R.; Graham, Stewart F.; Grant, Irene R.; Grover, Sunita; Green, Brian D.
Highlights: First demonstration that lactic acid bacteria interact with enteroendocrine cells. Certain strains elicit GLP-1 + GIP secretion and upregulate their gene expression. PCR array data implicate signalling agents of the toll-like receptor system. MyD88 expression decreased 23-fold and blockade of MyD88 triggers GLP-1 secretion. CD14 expression increased 17-fold and blocking CD14 prevents LAB-induced secretion. Abstract: Glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) are incretin hormones released from intestinal enteroendocrine (EE) cells and have well-established glucose-lowering actions. Lactic acid bacteria (LAB) colonise the human intestine, but it is unknown whether LAB and EE cells interact. Acute co-culture of LAB with EE cells showed that certain LAB strains elicit GLP-1 and GIP secretion (13-194-fold) and upregulate their gene expression. LAB-induced incretin hormone secretion did not appear to involve nutrient mechanisms, nor was there any evidence of cytolysis. Instead PCR array studies implicated signalling agents of the toll-like receptor system, e.g. adaptor protein MyD88 was decreased 23-fold and cell surface antigen CD14 was increased 17-fold. Mechanistic studies found that blockade of MyD88 triggered significant GLP-1 secretion. Furthermore, blocking of CD14 completely attenuated LAB-induced secretion. A recent clinical trial clearly shows that LAB have potential for alleviating type 2 diabetes, and further characterisation of this bioactivity is warranted.